Features of the reaction of the kidney function of healthy rats to the intake of boric hydrocarbonate sodium mineral waters of varying quantitative macro- and micro-composition - Nasibullin, B.; Gushcha, S.; Аrabadji, M.; Stepanova, V. (Journal of Education, Health and Sport, 2022)
The purpose of the work is a comparative assessment of the effect of boron hydrocarbonate sodium mineral waters with a varying quantitative and qualitative composition of macroelements and with different amounts of a bioactive element on the state of the urinary system of rats. Materials and methods. The work was performed on 81 white rats of the Wistar line of auto bred breeding, weighing 180-200 g. The rats were divided into four groups: group 1 - 21 intact rats served as controls; group 2 - 20 rats treated intragastrically with a soft probe MW "Polyana Ploskivskaya" at a dose of 1% of body weight daily, a course of 7 days; group 3 - 20 rats treated with MW "Polyana Kupel" according to the above method; group 4 - 20 rats treated with MW "Svalyava" according to the above process. Before removing the animals from the experiment, daily urine was collected from them; blood was also taken from the tail vein for biochemical studies. At autopsy, pieces of kidneys were taken for histological and histoenzymological studies (the activity of succinate dehydrogenase and lactate dehydrogenase was determined). Results. The histological studies showed no pathological changes in the kidneys were observed with the use of the studied boron MW. Still, there were structural changes, as well as an increase in the activity of redox enzymes. Changes in kidney function were unidirectional with using any of the investigated MW. Still, they had quantitative differences, which are less related to the amount of boron (in the form of orthoboric acid) in 1 liter of MW and more dependent on the osmolarity of the MW, the qualitative composition of macronutrients, and their ratio. Conclusion. We believe that osmolarity, as an integrated indicator of the state of the macronutrient component of MW, can be used to assess its effect on the structural and functional characteristics of the kidneys.